Label-free dengue detection utilizing PNA/DNA hybridization based on the aggregation process of unmodified gold nanoparticles - Abdul Rahman, Samsulida; Saadun, Rafidah; Azmi, Nur Ellina; Ariffin, Nurhayati; Abdullah, Jaafar; Yusof, Nor Azah; Sidek, Hamidah; Hajian, Reza (Hindawi Publishing Corporation, 2014)
A label-free optical detection method based on PNA/DNA hybridization using unmodified gold nanoparticles (AuNPs) for dengue virus detection has been successfully developed. In this study, no immobilization method is involved and the hybridization of PNA/DNA occurs directly in solution. Unmodified AuNPs undergo immediate aggregation in the presence of neutral charge peptide nucleic acid (PNA) due to the coating of PNA on AuNPs surface. However, in the presence of complementary targets DNA, the hybridization of PNA probe with target DNA forms negatively charged complexes due to the negatively charged phosphate backbone of the target DNA. The negatively charged complexes adsorbed onto the AuNPs surface ensure sufficient charge repulsion, need for AuNPs dispersion, and stability in solution. The detection procedure is a naked eye method based on immediate color changes and also through UV-vis adsorption spectra. The selectivity of the proposed method was studied successfully by single base mismatch and noncomplementary target DNA.